Efficacy of Smartphone-based Exercises in Conjunction with Modified Glasses Prescription in the Treatment of Convergence Insufficiency and Fusion Weakness. Issue 1 (2nd January 2019) - Mohan, Amit; Kaur, Navjot; Sen, Pradhnya; Jain, Elesh; Gajraj, Manju
ABSTRACT: Purpose : To determine the efficacy of Smartphone-based exercises in conjunction with modified glasses prescription in the treatment of convergence insufficiency and fusion weakness.Methods : A total of 150 patients using glasses and having asthenopia between 15 and 30 years of age were subjected to thorough eye examination including binocular vision testing and refraction. Of them 26 individuals were found to have convergence insufficiency with fusion weakness and exophoria >6 pd. Subjects with amblyopia, manifest strabismus and other ocular diseases were excluded from the study. Modified glasses (overcorrection of myopia by −0.5 D Sph & under correction of hypermetropia by +0.5 D Sph) were given along with newly designed Smartphone-based fusion exercises.Results : Near point of convergence improved by 2.89 ± 1.08 cm, positive fusion vergence by −10.2 ± 3.25 pd and near phoria by 3.13 ± 0.32 pd ( p < 0.001).Conclusion : The current study demonstrates the efficacy of Smartphone-based fusion exercises, in conjunction with modified glasses prescriptions, in the management of symptomatic convergence and fusion insufficiency. Indeed, this novel, newly designed approach for convergence insufficiency improves symptoms by reducing near point of convergence and degree of exophoria and increasing fusional vergence.